Strategi Pengembangan Bisnis Ikan Cupang - Tri Prihartatik; Eka Askafi; Ahsin Daroini (REVITALISASI : Jurnal Ilmu Manajemen, 2022)
Betta fish cultivation has been established since 1996 starting from the formation of the Karya Mina fish cultivator group in Ketami Village, Pesantren District, Kediri City. These cultivation activities continue to develop so that in 2022 the City of Kediri was confirmed as a Fisheries Village for Ornamental Fish Cultivation by the Ministry of Maritime Affairs and Fisheries. With the existing potential, the right strategy is needed in developing the Betta fish business. This research was conducted at Betta fish farming business locations covering 6 groups of fish cultivators in Ketami Village, Pesantren Village, Bawang Village, and Jamsaren Village, Pesantren District, Kediri City, using qualitative methods. Based on the SWOT analysis, it is known that the appropriate development strategy is the SO strategy. Further analysis uses QSPM to determine the priority of the existing alternative strategies. The main alternative strategy was found, namely Optimizing information technology for Betta type variants, production quantity, and cultivation techniques. The second alternative strategy is to open the market with various types and prices of betta. And the last alternative strategy is to utilize government support, other parties, and institutions for business development.